Agronomic performance of wheat cultivated for grain production and for dual‑purpose under crop‑livestock integration systems - dos Santos, Henrique Pereira; Fontaneli, Renato Serena; Caierão, Eduardo; Spera, Silvio Tulio; Vargas, Leandro (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess yield and yield components of wheat cultivated for grain production and for dual‑purpose under no‑tillage crop‑livestock integration systems (CLIS). Grain yield of the two wheat types and yield components for the grain type were evaluated in the 2003 to 2008 growing seasons, in a Rhodic Hapludox, in Coxilha, RS, Brazil, in the following systems: 1, wheat/soybean and common vetch/corn; 2, wheat/soybean and black oat pasture/corn; 3, wheat/soybean and black oat pasture/soybean; 4, wheat/soybean and field pea/corn; 5, wheat/soybean, dual-purpose triticale/soybean, and common vetch/soybean; and 6, wheat/soybean, dual-purpose white oat/soybean, and dual-purpose wheat/soybean. A randomized complete block design, with four replicates, was used. There were no differences between CLIS in yield components (number of spikes, number of grains per spike, and grain mass) of wheat for grain production in differentes CLIS. The systems 2, 3, 4, and 5 showed higher yield of the grain‑type wheat in comparison to 6. There are no significant differences in grain yield, hectoliter weight, and weight of 1,000 kernels between wheat cultivated for grain production and for dual-purpose.